8q22.2q22.3 Microdeletion Syndrome Associated with Hearing Loss and Intractable Epilepsy - Alejandra Rincon; Paola Paez-Rojas; Fernando Suárez-Obando (Case Reports in Genetics)
8q22.2q22.3 microdeletion syndrome has been described in only seven patients. We present a new case from Colombia. The characteristics of this condition are developmental delay, microcephaly, seizures, and typical facial dysmorphism. We discuss the clinical phenotype of the patient presenting relevant findings like hearing loss and severe epilepsy and the possible relations between the phenotype and the genes involved in the microdeletion. We describe a female with developmental delay, microcephaly, epilepsy, severe short stature, impaired speech, facial dysmorphism, and congenital deafness. A minimal/maximal deletion of 5.238 Mb and 5.374Mb, respectively, at 8q22.2q22.3 was diagnosed using a genome-wide array. The clinical phenotype is similar to the others seven patients previously reported; however, the severity of epilepsy and the concomitant hearing loss is remarkable, characteristics previously observed independently in only two patients. The KCNS2 gene is located in the deleted regions (8q22.2). Therefore it is a possible candidate for explaining the complex neurologic phenotype.